EFFECT OF FATIGUE ON THE RATE OF CONTRACTION AROUND THE KNEE AND FUNCTION IN FOOTBALLERS WITH A HISTORY OF ANTERIOR CRUCIATE LIGAMENT RUPTURE - Adnan Radi Faraj; Munadhil Adil Kasim (Proximus Journal Publishing, 2025)
Given that athletes endure fatigue after an anterior cruciate ligament rupture, it is crucial to comprehend the implications of fatigue on irreparable nerve regulation and functionality. This research aimed to examine the impact of fatigue on the contraction of knee circumferential muscles and functionality in athletes with a history of anterior cruciate ligament rupture. Materials and Methods: The sample included 24 athletes, categorised into three groups: 8 with ACLR repair, 8 with ACLD rupture without reconstruction, and 8 serving as a control group. The joint contraction of the quadriceps, hamstrings, and gastrocnemius was evaluated before and after exhaustion. Results: The quadriceps joint contraction rate in the afflicted groups (ACLR and ACLD) was considerably lower than that of the control group. The functionality in the single-leg Li test diminished markedly in the afflicted groups post-fatigue. Conclusion: The simultaneous contraction of the twin quadriceps is crucial for knee joint stability; hence, it is advisable to emphasise these muscles in rehabilitation activities. Due to the diminished functioning of injured athletes, it is advisable to assess functional tests under circumstances of exhaustion
Keywords: Fatigue; Rate of Contraction; Knee; Function